2011
DOI: 10.1111/j.1365-2427.2011.02708.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in ecosystem metabolism and food web carbon transfer in a wet‐dry tropical river

Abstract: 1. High light availability and stable base flow during the dry season promote primary production in perennial rivers of the wet-dry tropics, in contrast to production during the wet season which is often limited by turbidity and scouring. The Mitchell River of northern Queensland (Australia) was studied to understand controls on aquatic production and respiration in the dry season in relation to spatial and temporal gradients of light and temperature. 2. At three sites along the river, whole-ecosystem gross pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 53 publications
(129 reference statements)
3
49
1
Order By: Relevance
“…At our focal streams, estimated rates of GPP ranged from 0.00026 g O 2 m À2 d À1 to 13 g O 2 m À2 d À1 , exceeding the range of GPP recorded across six tropical studies (0.10-4.6 g O 2 m À2 d À1 ) [Gücker et al, 2009;Hunt et al, 2012;Mulholland et al, 2001;Oliver and Merrick, 2006;Ortiz-Zayas et al, 2005;Townsend et al, 2011]. Available light has been identified as a strong contributing factor to high GPP, especially in reference streams [Bernot et al, 2010;Mulholland et al, 2001;Young and Huryn, 1999].…”
Section: Stream Metabolic Dynamicscontrasting
confidence: 48%
See 1 more Smart Citation
“…At our focal streams, estimated rates of GPP ranged from 0.00026 g O 2 m À2 d À1 to 13 g O 2 m À2 d À1 , exceeding the range of GPP recorded across six tropical studies (0.10-4.6 g O 2 m À2 d À1 ) [Gücker et al, 2009;Hunt et al, 2012;Mulholland et al, 2001;Oliver and Merrick, 2006;Ortiz-Zayas et al, 2005;Townsend et al, 2011]. Available light has been identified as a strong contributing factor to high GPP, especially in reference streams [Bernot et al, 2010;Mulholland et al, 2001;Young and Huryn, 1999].…”
Section: Stream Metabolic Dynamicscontrasting
confidence: 48%
“…High stream respiration rates were particularly surprising because they occurred in a nonforest catchment. Previous studies suggest that forested catchments produce the greatest respiration rates as a result of high organic matter inputs from riparian vegetation and a tendency for pristine streams to retain organic matter [Delong and Brusven, 1994 [Gücker et al, 2009;Hunt et al, 2012;Mulholland et al, 2001;Oliver and Merrick, 2006;Ortiz-Zayas et al, 2005;Townsend et al, 2011]. In the mature oil palm stand in August 2009, low flow rates resulted from little antecedent precipitation.…”
Section: Stream Metabolic Dynamicsmentioning
confidence: 99%
“…Thus, terrestrial DOM via bacteria could be quite important to either zebra mussels or zooplankton. It is widely known that zooplankton can assimilate bacteria (Jansson et al 2007), and bacterial consumption by zebra mussels has been observed in the lab (Selegean et al 2001). That the zooplankton in the Hudson directly consume significant material of terrestrial origin would be consistent with laboratory studies that have shown that Daphnia can grow and reproduce on mixtures of terrestrial leaves and phytoplankton or on microbially colonized pollen grains alone (Brett et al 2009;Masclaux et al 2011).…”
Section: Discussionmentioning
confidence: 58%
“…As in the present study, Caraco et al (2010) found that both copepods and Bosmina had significant terrestrial support and that cladocerans were more dependent on terrestrial organic matter than were copepods. Several authors have suggested that zooplankton in lakes are often significantly subsidized by terrestrial inputs (Jansson et al 2007;Rautio et al 2011;Solomon et al 2011). The work in lakes can be complicated by the possibility of zooplankton feeding in the metalimnion, where the phytoplankton may be isotopically distinct from those in the surface water (Francis et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3). Barramundi also migrate upstream beyond the upper limits of where collections were made in the current study, and individuals from the main channel with elevated d 13 C indicative of floodplain and marine foraging have been observed as far as 200 km upriver of the delta (Hunt et al 2011), demonstrating the strong connectivity among habitats. This suggests an explanation for the link between flood magnitude and feeding and growth opportunities, partially explaining strong correlations between maximum annual river discharge and barramundi recruitment that were previously left to speculation (Robins et al 2006).…”
Section: Speciesmentioning
confidence: 92%